Using Assessment for Learning: Multi-Case Studies of Three Chinese University English as a Foreign Language (EFL) Teachers Engaging Students in Learning and Assessment - Wu, Xiaoming (Molly); Zhang, Lawrence Jun; Liu, Qian (Frontiers in Psychology, 2021)
Student engagement is an important issue in learning and teaching given its positive effects on students' learning outcomes. Assessment for Learning (AfL), an assessment and pedagogic innovation, if done well, can fully engage students in the learning and assessment process. Adopting a multi-case design, the present study explored how Chinese university English as a Foreign Language (EFL) teachers used AfL to facilitate student engagement in their classrooms and what factors influenced their AfL practices. Three EFL teachers were recruited on a voluntary basis from two universities in Northwest China. Data collected from semi-structed interviews, stimulated recall interviews, and classroom observations suggested that teacher participants demonstrated differed assessment practices, representing Assessment of Learning (AoL), convergent, and divergent AfL, respectively. Three factors: teacher assessment literacy, teachers' beliefs about the relationship between goal orientation and motivation, as well as a trusting relationship between teachers and students, were identified as contributing to teachers' different assessment practices. Our study calls for teacher educators' efforts to equip teachers with necessary assessment-related knowledge and skills, encourage teachers to negotiate learning goals with students, and help teachers establish a trusting environment in their classrooms, if AfL is to be fully embedded in classroom instruction.